Perception of Mothers on Adequate Nutrition - Valoo, Darshini; Diana, Aly; Gondodiputro, Sharon (Althea Medical Journal, 2017)
Background: Malnutrition in children less than 5 years old persists around the world. In West Java and one of the districts of West Java (Sumedang), the prevalence of malnutrition is about 18.5% and 15.8% respectively.Â  Numerous factors can lead to child malnutrition. Difficulties in availability, accessibility, acceptability and quality of food can be contributing factors. A good perception of mother on adequate nutrition can improve childrenâs nutritional status. This study was conducted to study the perception of mothers with children 2 to 5 years old on adequate nutrition. Methods: Most of the respondents had good perception on the aspect of adequate nutrition.Â  Results showed perception on availability was 83.8%, physical accessibility was 97.1%, economical accessibility was 98.6%, information accessibility was 84.8% and acceptability was 81.0%. However, perception of respondents on good quality nutrition for the main meal and additional food was still poor. Moreover, there are taboos for eating shrimp and watermelon. Additionally, children were given snacks in large amount.Results: There was a strong correlation between mid-upper arm muscle area/size and muscular strength (correlation cooefficient 0.746). Moreover, the higher the Body Mass Index, the stronger the muscle strength was to some point. If the BMI was more than 25 kg/m2, this findings did not occurred. Conclusions: This study reveals that the perception of mothers on good quality food is poor regardless the good results on availibility, accesibility and acceptability. [AMJ.2017;4(1):87â93]Â DOI:Â 10.15850/amj.v4n1.1027